Calculation of Mechanical Properties of BCC Ti-Nb Alloys; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Nikonov A. Yu.; Zharmukhambetova A. M.; Skripnyak N. V.; Ponomareva A. V.; Abrikosov I. A.; Barannikova S. A.; Dmitriev A. Yu. Andrey Yurievich (2015, 2015)
Title screen